The CIRC Learning Model in Improving Elementary School Students’ Reading Skills - Arfiansah Saparuddin; Ismah Damayanti (Journal of Primary Education Innovation and Research, 2025)
The low level of students’ reading ability has an impact on students’ difficulties in understanding reading texts. In reality, students’ reading comprehension ability remains low because students tend to feel bored quickly during the learning process. This study aims to determine the effect of implementing the Cooperative Integrated Reading and Composition learning model on reading comprehension ability. This model is used to improve students’ reading comprehension ability. This study employed a qualitative approach obtained through a literature review. Based on several literatures and studies conducted on the use of the CIRC learning model, there was an improvement in students’ reading comprehension ability. The use of the CIRC learning model can be considered highly successful in improving students’ reading comprehension ability.